PENGEMBANGAN MODUL MORFOLOGI TUMBUHAN MATERI DAUN (FOLIUM) PADA PROGRAM STUDI PENDIDIKAN BIOLOGI UNIVERSITAS PASIR PENGARAIAN - Dahlia, Dahlia; Pratiwi, Windi; Mubarrak, Jismi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasir Pengaraian, 2022)
This study aims to determine the feasibility of the plant morphology module for Biology Students Semester 3 for the 2021/2022 FKIP academic year at Pasir Pengaraian University. This research was carried out from May 2022 to January 2023. The type of research used is the ADDIE Research and Development model. The population in this study were all students of the Biology Education Study Program FKIP Pasir Pengaraian University for the 2021/2022 academic year. The sample in this study were 36 semester 3 students for the 2021/2022 academic year of the Biology Education Study Program. Data collection was carried out using a questionnaire and data were analyzed descriptively. The results showed that the plant morphology module for Semester 3 Biology students as a whole was declared